Preparation and characterization of a calcium–phosphate–silicon coating on a Mg–Zn–Ca alloy via two-step micro-arc oxidation. Issue 23 (31st May 2017) - Dou, Jinhe; Chen, Yang; Chi, Yiming; Li, Huancai; Gu, Guochao; Chen, Chuanzhong
Abstract : Magnesium alloys are the most promising implant materials due to their excellent biodegradability. Abstract : Magnesium alloys are the most promising implant materials due to their excellent biodegradability. However, their high degradation rate limits their practical application. In this study, we produced a calcium–phosphate (Ca–P) coating and a calcium–phosphate–silicon (Ca–P–Si) coating via one-step and two-step micro-arc oxidation processes, respectively. The microstructure and chemical composition of the MAO coatings were characterized using SEM, XRD and EDS. The degradation behaviors of the MAO coatings and the substrate were investigated using electrochemical techniques and immersion tests in simulated body fluid (SBF). The results show that the silicate was successfully incorporated into the Ca–P coating in the second MAO step, and this also increased the thickness of the coating. The Ca–P–Si coatings remarkably reduced the corrosion rate of the Mg alloy and Ca–P coating during 18 days of immersion in SBF. In addition, the bone-like apatite layer on the sample surface demonstrated the good biomineralization ability of the Ca–P–Si coating. Potentiodynamic polarization results showed that the MAO coating could clearly enhance the corrosion resistance of the Mg alloy. Moreover, we propose the growth mechanism of the MAO coating in the second step.